Suicide first aid guidelines for assisting persons from immigrant or refugee background: a Delphi study. (3rd July 2018) - Colucci, E.; Jorm, A. F.; Kelly, C. M.; Minas, H.
ABSTRACT: Objective: Suicide rates vary across different cultural groups and some immigrant or refugee populations display higher risk for suicide. This study aimed to produce guidelines to help members of the public provide assistance to a person from an immigrant or refugee background who is having suicidal thoughts or displaying suicidal behaviour. Method: The Delphi expert consensus method was used to identify warning signs and first aid actions to include in guidelines. Forty-four professionals and/or advocates with lived experience were asked to rate whether each statement contained in an online questionnaire should be included in the guidelines and to suggest additional statements considered by the respondent to be particularly relevant to a person from an immigrant or refugee background. The Delphi process started with 473 statements and 80 new items were written based on suggestions from panel members. Results: Out of the total 553 statements, 345 were endorsed as appropriate warning signs or helping actions. These statements were used to develop the guidelines. Discussion: The guidelines specific to people from immigrant or refugee backgrounds contain additional items to those included in similar guidelines for English-speaking countries. The guidelines may be used for gatekeeper training for suicide prevention in culturally diverse societies.